2009
DOI: 10.1249/mss.0b013e3181930c2b
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Performance and Vitamin D

Abstract: Vitamin D may improve athletic performance in vitamin D-deficient athletes. Peak athletic performance may occur when 25(OH)D levels approach those obtained by natural, full-body, summer sun exposure, which is at least 50 ng x mL(-1). Such 25(OH)D levels may also protect the athlete from several acute and chronic medical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
249
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(264 citation statements)
references
References 53 publications
7
249
2
6
Order By: Relevance
“…There are several possible explanations for this observation including the lower serum 25(OH)D which is also known to have an adverse effect on muscle function. 1,14,15 However we detected no significant associations between the rise in 25(OH)D from winter to summer and the fall in injury incidence. Although this may have been due to the relatively low power of the current study, there are other possible explanations.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…There are several possible explanations for this observation including the lower serum 25(OH)D which is also known to have an adverse effect on muscle function. 1,14,15 However we detected no significant associations between the rise in 25(OH)D from winter to summer and the fall in injury incidence. Although this may have been due to the relatively low power of the current study, there are other possible explanations.…”
Section: Discussioncontrasting
confidence: 71%
“…10 Dancers also demonstrate high incidence of injury which has been partly explained by inadequate levels of physical fitness, 11 particularly by low levels of muscular strength. 12,13 Inadequate muscular strength has been associated with vitamin D deficiency in athletes 14,15 and non-athletes 16,17 alike. However, Wang and DeLuca 18 suggested that the effect of vitamin D on muscle function might be indirect as they could not detect a known vitamin D receptor in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…This may be a result of a number of factors including the training intensity, age of subjects or other protective mechanisms within the cohort. In the mid-20th century athletes were supposedly using UV light as a performance aid, although scientific evidence to support its use was limited (29)(30)(31) . Severe 25(OH)D deficiency is known to be associated with reduced type II muscle fibre composition (44)(45)(46)(47) and the sarcopenia associated with ageing is thought to be affected by 25(OH)D concentrations (48)(49)(50) .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms in the bone protection repertoire of vitamin D also include reduction of the excessive bone remodeling that increases bone fragility, reduction in fracture rate, and improvement in neuromuscular function [4,37]. Reduction in fracture rate and improvement in neuromuscular function have been known for a long time from the finding that vitamin D-producing ultraviolet B irradiation improves athletic performance (for a review, see Cannell et al [9]). In fact, muscle power is associated with 25-hydroxyvitamin D levels [46].…”
Section: Importance Of Vitamin D To Musculoskeletal and Extraskeletalmentioning
confidence: 99%
“…Vitamin D not only controls calcium homeostasis and bone turnover [19] but also has been implicated in the risk of overall mortality [30], cancer [25], diabetes [25], musculoskeletal disorders [25], physical performance [9], hypertension [25], cardiovascular diseases [25], and autoimmune diseases [25]. However, no consensus exists concerning the minimum serum concentration of 25-hydroxyvitamin D necessary to guarantee optimal health.…”
Section: Introductionmentioning
confidence: 99%